Avaliação da atividade leishmanicida de macrófagos isolados de indivíduos tratados e assintomáticos para leishmaniose visceral - Passos, Cárcia Santana (2012)
Leishmaniasis is a serious public health problem worldwide, requiring effective measures for its control and treatment. Visceral leishmaniasis is the most severe form and has a lethal potential. Depending on the interaction between the parasite and the host immune response, different clinical manifestations may develop: asymptomatic, oligosymptomatic and symptomatic. Macrophages play a central role in immune response. However, their microbicidal activity may be impaired, leading to the survival and proliferation of the parasites inside them. The objective of this study was to evaluate the leishmanicidal activity of macrophages isolated from treated and asymptomatic visceral leishmaniasis subjects after infection by Leishmania chagasi. Our hypothesis was that macrophages isolated from treated subjects were more susceptible to infection by Leishmania chagasi in relation to asymptomatic patients. From a cross-sectional study, 05 symptomatic patients and 02 asymptomatic were investigated at University Hospital. Mononuclear cells were isolated from peripheral blood of 07 patients in order to obtain monocytes and further differentiation into macrophages. These were infected with the isolated LVHSE-07 from L. chagasi for 2, 72 and 96 hours in conditions with and without stimulus of LPS and IFN-. To examine whether macrophages responded differently to the symptomatic patient's own Leishmania, 03 symptomatic and 02 asymptomatic patients were reconvened, so that their macrophages would be infected with Leishmania from symptomatic patients (LVHSE-24, LVHSE-28, LVHSE-37). Leishmanicide response of macrophages was assessed by determining the percentage of infected macrophages and the number of amastigotes inside macrophages. The results suggest that the macrophages of the symptomatic patients were more infected, especially when used patient's own Leishmania, and they did not control infection, even in the presence of stimulus, unlike asymptomatic's macrophages, which controlled infection, independently of what Leishmania was used. This study demonstrated that macrophages from symptomatic patients are more susceptible to infection by Leishmania chagasi, when compared with macrophages from asymptomatic patients; macrophages from symptomatic patients are more infected with their own isolated of L. chagasi; macrophages from asymptomatic patients are less infected with L. chagasi and have a parasitic load lower than the macrophages of symptomatic patients, regardless of the Leishmania isolated used in infection. It follows that macrophages are related to susceptibility or resistance to infection by Leishmania chagasi.